Melatonin modulates Nrf2 activity to protect porcine pre‐pubertal Sertoli cells from the abnormal H2O2 generation and reductive stress effects of cadmium. Issue 1 (24th May 2022) - Bartolini, Desirée; Arato, Iva; Mancuso, Francesca; Giustarini, Daniela; Bellucci, Catia; Vacca, Carmine; Aglietti, Maria Chiara; Stabile, Anna Maria; Rossi, Ranieri; Cruciani, Gabriele; Rende, Mario; Calafiore, Riccardo; et al.
Abstract: Melatonin (MLT) is a cytoprotective agent holding potential to prevent cadmium (Cd) toxicity and its impact in testicular function and fertility. In this study, we explored such potential in porcine pre‐pubertal Sertoli cells (SCs). Cd toxicity resulted in impaired SC viability and function, abnormal cellular H2 O2 generation and efflux, and induction of reductive stress by the upregulation of Nrf2 expression and activity, cystine uptake and glutathione biosynthesis, glutathione‐S‐transferase P (GSTP) expression, and protein glutathionylation inhibition. Cd toxicity also stimulated the activity of cellular kinases (MAPK‐ERK1/2 and Akt) and NFkB transcription factor, and cJun expression was increased. MLT produced a potent cytoprotective effect when co‐administered with Cd to SCs; its efficacy and the molecular mechanism behind its cytoprotective function varied according to Cd concentrations. However, a significant restoration of cell viability and function, and of H2 O2 levels, was observed both at 5 and 10 μM Cd. Mechanistically, these effects of MLT were associated with a significant reduction of the Cd‐induced activation of Nrf2 and GSTP expression at all Cd concentrations. CAT and MAPK‐ERK1/2 activity upregulation was associated with these effects at 5 μM Cd, whereas glutathione biosynthesis and efflux were involved at 10 μM Cd together with an increased expression of the cystine transporter xCT, of cJun and Akt and NFkB activity. MLT protects SCs from Cd toxicity reducing its H2 O2 generation and reductive stress effects. A reduced activity of Nrf2 and the modulation of other molecular players of MLT signaling, provide a mechanistic rational for the cytoprotective effect of this molecule in SCs.